2021
DOI: 10.1063/5.0077629
|View full text |Cite
|
Sign up to set email alerts
|

Surface charge mediated polar response in ferroelectric nanoparticles

Abstract: Interfacial phenomena in dielectric-ferroelectric composites have significant potential for promoting novel properties. Here, we utilize a dynamic Landau–Ginzburg–Devonshire methodology to elucidate the influence of an electrostatic self-interaction on the polarization behavior of spherical ferroelectric nanoparticles embedded in a dielectric matrix. By varying the particle volume and the dielectric permittivity of the surrounding medium, phase boundaries between states with polarization patterns exhibiting mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…To check whether our observations were consistent with the underlying texture of the volume polarization, we conducted phase field simulations. 15,17 These simulations revealed that in the equilibrium state at the temperature of 293 K, a polar axis (OZ c ) with up and down 180°domains emerges in the core, accompanied by 90°domains on the two surfaces normal to this axis in a layer of an average thickness of 8 nm. In this layer, there is a dominant polarization orientation in the plane with mostly 180°and a few 90°domains (on the edges).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…To check whether our observations were consistent with the underlying texture of the volume polarization, we conducted phase field simulations. 15,17 These simulations revealed that in the equilibrium state at the temperature of 293 K, a polar axis (OZ c ) with up and down 180°domains emerges in the core, accompanied by 90°domains on the two surfaces normal to this axis in a layer of an average thickness of 8 nm. In this layer, there is a dominant polarization orientation in the plane with mostly 180°and a few 90°domains (on the edges).…”
Section: Discussionmentioning
confidence: 96%
“…These topological defects are often endowed with rich properties, such as negative dielectric capacitance, an effect envisioned to reduce field effect transistor energy consumption. The polarization texture in 0-dimensional ferroelectric crystals, that is, ferroelectric nanodots and nanocrystals (NCs), have been less studied; yet, recent (mainly simulation) studies have reported exotic polarization textures in NCs as well. …”
Section: Introductionmentioning
confidence: 99%
“…One of the first theoretical predictions of the topological polar phase was made in the 2000s, where the polar vortex phase was predicted in the low dimensional ferroelectric system (i.e., PZT nanodisks, nanorods, and thin films) via ab initio calculations (Figure 3a). [ 101,102 ] Consequently, other theoretical studies have been reported on the vortex structure, [ 103–125 ] switching dynamics, [ 126–141 ] and properties [ 142–146 ] in various low‐dimensional ferroelectric systems. In particular, in 2006, using phase‐field simulations, J. Wang et al predicted the formation of polar vortex‐like structure in a ferroelectric nanodot (Figure 3b).…”
Section: Topological Polar Structuresmentioning
confidence: 99%